Association of factor V activity with risk of venous thromboembolism and atherothrombotic cardiovascular events: A retrospective population-based cohort study. Issue 168 (August 2018) - Saliba, Walid; Warwar, Amir; Kotler, Antonio; Cohen, Shai; Stein, Nili; Rennert, Gad; Ornstein, Deborah L.; Preis, Meir
Abstract: Introduction: Factor V (FV) deficiency is a rare inherited coagulation disorder associated with bleeding tendency. As a result, it has been postulated that decreased FV activity may confer protection against venous thromboembolism and atherothrombotic cardiovascular events. Materials and methods: Using the electronic database of the largest health care provider in Israel, we identified all adult individuals who were tested for FV activity between January 2004 and June 2017. Subjects with liver cirrhosis or FV Leiden mutation were excluded. FV activity was classified into three predefined categories; FV activity >50%, FV activity 30–50%, and FV activity ≤30%. Patients were followed from January 2004 to June 2017 for new atherothrombotic cardiovascular events (composite of myocardial infarction, stroke, and TIA) and venous thromboembolism (VTE). Results: Overall 2021 individuals were included; 83.2% had FV activity >50%, 9.6% FV activity 30–50%, and 7.2% had FV activity ≤30%. Compared to individuals with FV activity >50% the adjusted HR for atherothrombotic cardiovascular events was 1.10 (95% CI, 0.63–1.90) in those with FV activity 30–50%, and 0.95 (0.49–1.8) in those with FV activity ≤30%. None of the patients with FV activity 30–50% had VTE during follow-up; therefore those with FV activity ≤50% were classified into one group. VTE incidence was lower in those with FV activity ≤50% compared to those with FV >50% activity; adjusted HR = 0.28 (0.09–0.91). Conclusion: This study suggests that decreased FV activity might be associated with decreased incidence of VTE. No significant association appears to exist between FV activity and atherothrombotic cardiovascular events. Highlights: Factor V activity ≤30% seems to be frequent in Israel Decreased factor V activity might be associated with lower risk of VTE Factor V activity is not associated with the risk of cardiovascular events